EFFECTIVENESS OF THE JOINT INVESTIGATION TEAM AS AN INSTRUMENT FOR GATHERING AND EXCHANGE OF EVIDENCE IN CROSS-BORDER INVESTIGATIONS - Manojlović Nedeljković, Milena; Lukić Radović, Maja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
This paper considers primarily the legal framework for the formation and functioning of a joint investigation team at the level of the European Union, with an emphasis on the consequences that these rules can have on the shaping of the legislative framework of the Republic of Serbia in this area, which also represents the subject of the authors' analysis, dedicating special attention to practical considerations in the process of setting up of a joint investigation team and to original elements of this progressive tool of international cooperation. The second focal point of this paper rests on the support that may be provided by Eurojust in the process of formation and functioning of joint investigative teams whose participants include both European union Member States and non EU countries, and the authors' reflection considers also the cooperation of the Republic of Serbia with Eurojust and includes the consideration of the opportunities for further strengthening of international cooperation with the Member States of the European Union after the signing of the Cooperation Agreement between Eurojust and the Republic of Serbia in 2019, mentioningsuccessful example of joint investigation teams that were supported by Eurojust, as the illustration of the advantages of this instrument of international cooperation.
Keywords: judicial cooperation; mutual legal assistance; cross-border investigations; joint investigation teams; European Union; Eurojust